A systemic review and meta-analysis of the effect of virtual reality training on balance in the elderly to prevent falls - Bhise, Swati; Rathi, Manisha; Shiralkar, Madhura; Dabadghav, Rachana; Bagade, Tanmay (Rzeszów University Press, 2025)
Introduction and aim. Virtual reality (VR) is used in various healthcare treatments. This review evaluates virtual reality therapy (VRT) for balance rehabilitation to prevent falls in older adults. Material and methods. Randomised control trials from January 2013 to May 2024 were searched in databases like PubMed and Web of Science. Data were extracted and analysed using RevMan 5.4 software. Analysis of the literature. The review included 12 studies with an average of 56 participants aged 50-80 years. Treatments last ed 4–10 weeks with 2-5 sessions per week, each 30-60 minutes. Meta-analyses of five studies using the berg balance scale (BBS) showed a weak impact on balance (Z=2.07, p=0.04; SMD=1.05, 95% CI [0.06, 2.05], p<0.0001). Conversely, the Timed Up and Go (TUG) test showed a more positive impact (Z=2.25, p=0.02; SMD=-0.74, 95% CI [-1.39, -0.09], p<0.001), with a difference of 4.4 higher in the experimental group than the control group. Conclusion. VRT shows promising effects in balance and gait training for older adults, but further clinical trials are needed to compare its impact with other therapies.
Dr. D. Y. Patil Deemed University’s ethics committee has approved the study under the reference DYPV/EC/448/2020.
Keywords: virtual reality; balance; ageing; BBS; TUG